2021
DOI: 10.3356/jrr-20-39
|View full text |Cite
|
Sign up to set email alerts
|

Expert Perceptions of Conflicts in African Vulture Conservation: Implications for Overcoming Ethical Decision-Making Dilemmas

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…According to Becker et al ( 2020 ) conservation practices can be refined by studying the microbiome of the vultures. Yee et al ( 2021 ) have suggested examining ethical perspectives of the stakeholders responsible for conservation for effective decision making in conservation. Complementation of national and global efforts is the key for effective conservation (Santangeli et al 2020 ).…”
Section: Conservation Programs and Future Strategiesmentioning
confidence: 99%
“…According to Becker et al ( 2020 ) conservation practices can be refined by studying the microbiome of the vultures. Yee et al ( 2021 ) have suggested examining ethical perspectives of the stakeholders responsible for conservation for effective decision making in conservation. Complementation of national and global efforts is the key for effective conservation (Santangeli et al 2020 ).…”
Section: Conservation Programs and Future Strategiesmentioning
confidence: 99%